Eugenic Feminism : Reproductive Nationalism in the United States and India - Nadkarni, Asha (Book collections on Project MUSE., 2014)
Asha Nadkarni contends that whenever feminists lay claim to citizenship based on women's biological ability to 'reproduce the nation', they are participating in a eugenic project - sanctioning reproduction by some and prohibiting it by others. Employing a wide range of sources from the United States and India, the book shows how the exclusionary impulse of eugenics is embedded within the terms of nationalist feminism.